Dentin hypersensitivity treatment of non-carious cervical lesions - a single-blind, split-mouth study - Simone da Silva FREITAS; Lucas Lopes Araújo SOUSA; José Machado MOITA NETO; Regina Ferraz MENDES; Raimundo Rosendo PRADO JUNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This study aims to compare the in vivo effect of a desensitizing therapy associated with a restorative technique for the treatment of cervical dentin hypersensitivity (CDH) in non-carious lesions. The sample consisted of 68 teeth with moderate or severe dentin hypersensitivity in 17 individuals (one tooth per quadrant). The sensitivity levels of the teeth were scored, and the teeth were randomly distributed into four groups: T1 - desensitizing gel applied once per week until remission of pain; T2 - desensitizing gel applied once per week followed immediately by restoration with resin composite (Filtek Z250, 3M Espe); T3 - desensitizing gel once per week until remission of pain and then restoration with resin composite; and T4 - restoration with resin composite. Dentin hypersensitivity was assessed at 0, 7, 30, 90 and 180 days. The Kruskal-Wallis, Wilcoxon and Mann-Whitney (p< 0.05) tests were used to compare the treatments. The mean baseline CDH scores were T1 - 2.41, T2 - 2.41, T3 - 2.47, and T4 - 2.70 (p > 0.05). At seven and 180 days, the mean CDH scores were as follows: T1 - 1.47/0.65, T2 - 1.35/0.71, T3 - 0.71/0.53, and T4 - 1.12/0.59, all of which were significantly lower (p< 0.001) than the baseline scores. The scores at 30, 90 and 180 days were not significantly different when compared to the score of the previous period. At 180 days, CDH scores were similar among groups (p> 0.05). Teeth with moderate or severe hypersensitivity that required a filling responded similarly regardless of whether the desensitizing procedure was carried out prior to the filling.